1996
DOI: 10.2527/1996.744799x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibilities of a corn-soybean meal diet as influenced by Bacillus products fed to finishing swine.

Abstract: Twelve crossbred barrows (initial BW of 59.7 kg) were used in nutrient balance trials to investigate the influence of adding two Bacillus products (Biomate 2B and Pelletmate Livestock, Chr. Hansen's Biosytems) to a 14% CP corn-soybean meal diet (.64% lysine, .6% Ca and .5% P). A 3 x 3 Latin-square design with an extra period was used. Treatments were as follows: 1) basal diet; 2) basal + Biomate 2B (BAC1); and 3) basal + Pelletmate Livestock (BAC2). After a 7-d adaptation to metabolism crates, each 10-d period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
25
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 0 publications
11
25
0
2
Order By: Relevance
“…This indicates that the tendency for improved ADG may have occurred as a result of a significant improvement in the ADFI, but not in digestibility. Our results confirm the findings of Kornegay and Risley (1996), who evaluated the effects of two Bacillus products (Biomate2B ® , comprised of B. subtilis CH201 and B. licheniformis CH200 and Pelletmate Livestock ® , comprised of B. subtilis, B. licheniformis and Bacillus pumilus) in the diets of finishing pigs and found no impact on the digestibility of nutrients (DM and N). Conversely, Min et al (2004) reported that positive effects in the DM and N digestibilities were observed in nursery pigs fed diets that were supplemented with 0.04% BioPlus 2B ® .…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that the tendency for improved ADG may have occurred as a result of a significant improvement in the ADFI, but not in digestibility. Our results confirm the findings of Kornegay and Risley (1996), who evaluated the effects of two Bacillus products (Biomate2B ® , comprised of B. subtilis CH201 and B. licheniformis CH200 and Pelletmate Livestock ® , comprised of B. subtilis, B. licheniformis and Bacillus pumilus) in the diets of finishing pigs and found no impact on the digestibility of nutrients (DM and N). Conversely, Min et al (2004) reported that positive effects in the DM and N digestibilities were observed in nursery pigs fed diets that were supplemented with 0.04% BioPlus 2B ® .…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings have been reported in studies when probiotics were given to piglets (Choi et al, 2011) and growing-finishing pigs (Gebru et al, 2010;Meng et al, 2010). There are also reports that probiotics have no positive effects on ADG and feed conversion of pigs (Kornegay and Risley, 1996;Estienne and Hartsock, 2005); this may be caused by different probiotic strains used in the experiments. These results show the enormous potential of probiotics as green growth promoters in finishing pig production.…”
Section: Discussionsupporting
confidence: 83%
“…However, probiotics supplementation to piglets to improve growth performance has shown variable results, and the precise mode of action through which probiotics exert their positive influence remains uncertain (Turner et al, 2001). No difference in growth performance was observed for pigs fed diets with added Lactobacilli (Harper et al, 1983) or Bacilli (Kornegay and Risley, 1996). However, improved growth performance and reduced incidence of E. coli in faeces was noted when Lactobacilli or Bacillus spp.…”
Section: Discussionmentioning
confidence: 86%